Concurrency of Early-Age Exposure to Chinese Famine and Diabetes Increases Recurrence of Ischemic Stroke - Suo, Yue; Chen, Weiqi; Pan, Yuesong; Li, Hao; Meng, Xia; Li, Zixiao; Wang, Chunjuan; Jing, Jing; Wang, Yilong; Wang, Yongjun (Frontiers in Neurology, 2021)
Background and Purpose Early age exposure to the Chinese Great Leap Forward famine (1959-1961) has been associated with the incidence of risk factors for ischemic stroke. This study aims to examine the relationship between early age famine exposure and 12-month stroke recurrence. We sought to explore the interaction between famine exposure status and metabolic phenotypes on stroke recurrence and how the adherence of crucial evidence-based key performance index (KPI) would modify this interaction. Methods We analyzed data of patients who were born between 1953 to 1964 in the China National Stroke Registry II (CNSR-II). The study population was further divided into five subgroups for comparing 12-month stroke recurrence. Multivariate Cox proportional hazard regression model was used in analyzing the impact of the concurrence of metabolic phenotypes (type 2 diabetes (T2D) or metabolic syndrome (MetS) and early-age famine exposure on recurrent risk. The influence of the adherence to predefined key performance index (KPI), and concurrency of metabolic phenotype was also evaluated. Results Concurrent T2D and early age famine exposure were associated with an increased recurrence risk of ischemic stroke with 12-month (adjusted hazard ratio (HR):1.63, 95% confidence interval (CI) 1.28-2.07). Optimal adherence to KPI was not associated with significantly reduced risk of 12-month stroke recurrence (adjusted HR: 0.80, 95%CI:0.51-1.26). Conclusions Concurrency of early-age famine exposure and diabetes mellitus was associated with a higher risk of stroke recurrence within 12 months, adherence to evidence-based KPI did not reduce the risk significantly.